Salience of Debt and Homebuyers' Credit Decisions - Sumit Agarwal; Artashes Karapetyan (Norges Bank, 2016)
We show how a regulatory disclosure of hidden debt can eliminate a large mispricing in housing. In a setting where homebuyers must combine several sources of debt, they are biased towards hidden loans, especially if they are young, or have no experience in financial investments or home acquisition. By reducing the mispricing of units with hidden debt, the increased salience of debt benefited homebuyers, particularly those that suffered most from it. An average homebuyer could save dollar18,000 by acquiring a dwelling with a one standard deviation lower debt. We confirm that lack of salience was the source of the bias, by showing that the regulation nearly eliminated the mispricing.
hdl:11250/2495795
Keywords: D12; G14; G21; G32; 330; salience; housing; cooperatives; mortgage; household finance; mispricing